[x-25]:3=21+6,2x5
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) \(\dfrac{24}{25}-x=\dfrac{3}{5}\)
\(x=\dfrac{24}{25}-\dfrac{3}{5}\)
\(x=\dfrac{24}{25}-\dfrac{15}{25}\)
\(x=\dfrac{9}{25}\)
b) \(\dfrac{4}{7}-\dfrac{x}{21}=\dfrac{10}{21}\)
\(\dfrac{x}{21}=\dfrac{4}{7}-\dfrac{10}{21}\)
\(\dfrac{x}{21}=\dfrac{12}{21}-\dfrac{10}{21}\)
\(\dfrac{x}{21}=\dfrac{2}{21}\)
\(x=2\)
a) 24/25 - x = 3/5
x =24/25 - 3/5
x = 24/25 - 15/25
x = 9/15
x = 3/5
Vậy x = 3/5
b)4/7 - x/21 = 10/21
x/21 = 4/7 - 10/21
x/21 = 12/21 - 10/21
x/21 = 2/21
vậy x = 2
----------------nếu thấy đúng thì cho mình xin 1like nhó-------------------------
a: \(=\left(\dfrac{3}{4}+\dfrac{1}{4}\right)+\left(\dfrac{18}{21}+\dfrac{3}{21}\right)+\dfrac{19}{32}+\dfrac{13}{32}=1+1+1=3\)
b: \(=35\cdot1.1\cdot25\cdot\left(7,5-7,5\right)=0\)
a: =(34+14)+(1821+321)+1932+1332=1+1+1=3=(43+41)+(2118+213)+3219+3213=1+1+1=3
b: =35⋅1.1⋅25⋅(7,5−7,5)=0=35⋅1.1⋅25⋅(7,5−7,5)=0
` 1, 5 . ( -2/25 = 3/2 . (-2)/25 = -6/50 = -3/25 `
` 1 3/5 . (-3)/4 = 8/5 . (-3)/4 = -24/20 = -6/5 `
`-15/4 : 21/(-1) = -15/4 . (-1)/21 = 15/84 = 5/28 `
` ( -2 1/7 ) : ( -1 1/14 ) = (-15)/7 : (-15)/14 = -15/7 . (-14)/15 = 210/105 = 2 `
`@animephamdanhv.`
a, <=> (x-5/100) -1 +(x-4/101) -1 +(x-3/102) -1= (x-100/5) -1+(x-101/4) -1 +(x-102/3) -1
<=> (x-105)(1/100 +1/101 +1/102)= (x-105)(1/5+1/4+1/3)
<=> (x-105)(1/100+1/101+1/102-1/5-1/4-1/3)=0
vì 1/100+1/101+1/102-1/5-1/4-1/3 khác 0 <=> x-105=0
<=> x=105
b, 29-x/21 +1+27-x/23 +1+25-x/25 +1+23-x/27 +1+21-x/29 +1=0
<=> 50-x/21 +50-x/23 +50-x/25 +50-x/27 +50-x/29=0
<=> (50-x)(1/21 +1/23 +1/25 +1/27 +1/29)=0
vì 1/21+1/23+1/25+1/27+1/29 lớn hơn 0
nên 50-x=0
<=> x=50
3. ( x - 6) = 25 - 7
3.(x - 6 ) = 18
x - 6 = 18 : 3
x - 6 = 6
x = 12
4.(x - 9) - 7 = 21
4.(x - 9) = 28
x - 9 = 7
x = 7 + 9 = 16
`# \text {DNamNgV}`
`3(x - 6) + 7 = 25`
\(\Rightarrow3\left(x-6\right)=25-7\\\Rightarrow3\left(x-6\right)=18\\ \Rightarrow x-6=18\div3\\ \Rightarrow x-6=6\\ \Rightarrow x=6+6\\ \Rightarrow x=12 \)
Vậy, `x = 12.`
___
`4(x - 3^2) - 7 = 21`
\(\Rightarrow4\left(x-9\right)=21+7\\ \Rightarrow4\left(x-9\right)=28\\ \Rightarrow x-9=28\div4\\ \Rightarrow x-9=7\\ \Rightarrow x=7+9\\ \Rightarrow x=16\)
Vậy, x = 16.`
\(21+\left(25-2\times X\right):3=26\\ \left(25-2\times X\right):3=26-21\\ \left(25-2\times X\right):3=5\\ 25-2\times X=5\times3\\ 25-2\times X=15\\ 2\times X=25-15\\ 2\times X=10\\ X=10:2\\ X=5\)
21 + ( 25 - 2 x X ) : 3 = 26
( 25 - 2 x X ) : 3 = 5
25 - 2 x X = 15
2 x X = 10
X = 5
Vậy x = 5.
\(\left(x-25\right)\)\(:3=21+31=52\)
\(x-25=52.3=156\)
\(x=156+25=181\)
TTiicccckk
(x - 25) : 3 = 21 + 31
(x-25) : 3 = 52
x - 25 = 52 x 3
x - 25 = 156
x = 156 + 25
x = 181